2006
DOI: 10.1103/physreve.73.057103
|View full text |Cite
|
Sign up to set email alerts
|

Linear irreversible thermodynamics and coefficient of performance

Abstract: Following the recent proposal by Van den Broeck for a heat engine [Phys. Rev. Lett. 95, 190602 (2005)], we analyze the coefficient of performance of a refrigerator in two working regimes using the tools of linear irreversible thermodynamics. In particular, one of the analyzed regimes gives a coefficient of performance which could be considered as the equivalent to the Curzon-Ahlborn efficiency. Also we consider the relation with the Clausius inequality, and some results for the relevant thermodynamic magnitude… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 8 publications
0
42
0
Order By: Relevance
“…Practically since the beginning of FTT as an active discipline, the limited validity of the CA-efficiency was established [3][4][5][6][7]. Nonetheless, at the end of the 1980's the CAefficiency was found linked to MW reversible cycles [13,14] and recently with its role in microscopic [11], mesoscopic [12] and macroscopic thermal cycles [8,9], and therefore the CA-efficiency has gained new insights, that have to do with a possible universality at least at the first few terms in the Taylor expansion of the efficiency as a function of η C = 1 − τ [12,19,21,23]. Clearly, Eq.…”
Section: ∆S =ˆTmentioning
confidence: 99%
See 1 more Smart Citation
“…Practically since the beginning of FTT as an active discipline, the limited validity of the CA-efficiency was established [3][4][5][6][7]. Nonetheless, at the end of the 1980's the CAefficiency was found linked to MW reversible cycles [13,14] and recently with its role in microscopic [11], mesoscopic [12] and macroscopic thermal cycles [8,9], and therefore the CA-efficiency has gained new insights, that have to do with a possible universality at least at the first few terms in the Taylor expansion of the efficiency as a function of η C = 1 − τ [12,19,21,23]. Clearly, Eq.…”
Section: ∆S =ˆTmentioning
confidence: 99%
“…Through their papers on reversible cycles performing at MW, LL [13,14] established a bridge with FTT-MPcycles, basically by means of the CA-efficiency. In recent years several authors [8][9][10][19][20][21][22][23] have renewed the interest on the CA-efficiency. The discussion on this famous formula has been mainly turned on to its possible universal nature within the context of finite-time cycles.…”
Section: ∆S =ˆTmentioning
confidence: 99%
“…A heat pump must transfer heat in a finite time and similar to the efficiency at maximum power for the motor we must find the coefficient of performance of the heat pump, under conditions of maximum heat transfer from the cold to the hot bath. Following Van den Broeck's work [18], regarding the efficiency at maximum power for the motor, some authors have investigated the coefficient of performance of the refrigerator at maximumQ 1→2 (∆T /T ) [20]. This quantity is maximum at a temperature difference ∆T * , given by…”
Section: (F/t and ∆T /Tmentioning
confidence: 99%
“…In a recent work, Van den Broeck [18] has shown that in the linear response regime, the efficiency at maximum power of a Brownian engine reaches the efficiency of an endoreversible engine when it operates at maximum power, namely the Curzon-Ahlborn efficiency [19]. Corresponding to the efficiency at maximum power, some authors have studied the equivalent quantity for the heat pump using linear irreversible thermodynamics [20]. Analytical expressions for the efficiency at maximum power [18,[21][22][23] and the corresponding quantity for a heat pump have been derived but the validity of these expressions have not been confirmed for the BL heat engine/heat pump for a finite mass of the Brownian particle.…”
Section: Introductionmentioning
confidence: 99%
“…Thus additional research work [27][28][29][30] has been devoted to obtain model-independent results on efficiency and COP using the well founded formalism of linear irreversible thermodynamics (LIT) for both cyclic and steadystate models including explicit calculations of the Onsager coefficients using molecular kinetic theory [31][32][33]. Beyond the linear regime a further improvement was reported by Izumida and Okuda [34] by proposing a model of minimally nonlinear irreversible heat engines described by extended Onsager relations with nonlinear terms accounting for power dissipation.…”
mentioning
confidence: 99%